(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Liver diseases represent a broad group of pathological conditions that affect the structure and function of the liver, one of the body’s most vital organs. These disorders may arise due to viral infections, metabolic dysfunction, toxic exposure, autoimmune processes, or hereditary factors. Early identification and timely intervention play a crucial role in preventing complications such as cirrhosis, hepatic failure, and hepatocellular carcinoma. This article provides an overview of the major types of liver diseases, their etiological factors, clinical manifestations, and the significance of early diagnosis and prevention strategies.